Souveraineté et interdépendance dans le nouvel ordre économique international - Bernier, Ivan (Études internationales, 1978)
The concept of a new international economic order remains ambiguous not only in the sphere of economies, which has already been demonstrated, but also from a juridical point of view. To further explore the latter aspect, the author considers the principal texts treating the new international economic order and seeks to identify the juridical bases thereof. Three main trends emerge : the first propounds a very absolutist conception of sovereignty, the second invokes the world government model, and the third, claiming middle ground between the previous two, aims toward a regrouping of individual sovereignties within collective structures better able to safeguard common interests. But it is still too early to say which of these approaches will hold away. For the moment, the current legal order obtains with, at the very most, some adjustments.